Bilateral congenital flank hernias due to complete lateral abdominal wall muscular agenesis - Andrew J. Hu; Martha Conley Elizabeth Ingram; Guillermo Ares; Mehul V. Raval; Seth D. Goldstein (Elsevier, 2021)
We report a case of a 4-week-old female presenting with congenital bilateral flank hernias. The patient was born at term and was found to have large bilateral flank bulges. Although her hernias were asymptomatic, bilateral lower extremity jerking movements prompted further workup which revealed thoracolumbar spinal cord dysraphism. No other congenital anomalies were identified. Given the low risk of incarceration, repair was delayed until 9 months of age. At operation, complete bilateral agenesis of the oblique and transversus abdominus musculature was found. Open repair was performed with bilateral latissimus dorsi rotational muscle flaps and biological mesh. Congenital flank hernias are extremely rare with few cases reported in the literature. While they can appear externally similar to the more widely reported congenital lumbar hernia, the herniation through the absent oblique and transversus musculature makes this case anatomically distinct. The exact etiology of congenital flank hernias is unclear, although given the presence of associated congenital anomalies, migrational failure during embryogenesis represents a likely culprit. Surgeons approaching this pathology should understand the importance of a thorough multidisciplinary evaluation for associated anomalies prior to operation and be familiar with complex hernia repair techniques such as rotational flaps.